The effectiveness of using information gap activities to promote grade 10 students’ participation in speaking lessons at Nguyen Dang Dao high school, Bac ninh province = Hiệu quả của việc sử dụng hoạt động điền thông tin nhằm tăng cường sự tham gia của họ - Nguyễn, Thị Hường (University of Languages and International Studies, 2017)
Electronic Resources